The Influence of Social Media Marketing and Word of Mouth on Brand Awareness at Gampung Aceh Café - Dinda Putri Zuniar; Mahir Pradana (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
The business world of the culinary industry is expanding quickly. One type of culinary business that entrepreneurs are particularly interested in is the café. As a result, effective promotion is required to raise customer awareness of the brand. A café called Gampung Aceh serves modernized Acehnese cuisine. The goal of this study was to examine the impact of social media marketing and word-of-mouth on brand recognition at the Gampung Aceh café. In this study, descriptive research kinds are combined with quantitative research methods. With a total of 400 respondents, samples were drawn using a non-probability sampling technique. Using IBM SPSS Statistics 23, data were examined using descriptive analytic approaches, traditional assumption tests, multiple linear regression analysis, and hypothesis testing. According to the findings of the descriptive study, 85.1% of the social media marketing variables fall under the very good group. Brand awareness and word-of-mouth variables are both included in the very good category with percentages of 87.2% and 86.6%, respectively. The impact of social media marketing and word-of-mouth advertising on brand awareness simultaneously as shown by multiple linear regression analysis is 68.8%. While additional factors not considered in this study might have an impact on the remaining 31.2%..